Physical properties and microstructure of butter cake added with Persea americana puree - Marina A.M.,; Nurhanan A.R.,; Wan Rosli W.I.,; Nurul Ain O., (Penerbit Universiti Kebangsaan Malaysia, 2016)
The effect of addition of avocado (Persea americana) puree on the physical and microstructure of butter cake was studied. Butter cakes were made by replacing butter with 10, 30 and 50% of avocado puree. Physical properties including batter specific gravity, volume, colour and image analysis of cellular structure of the crumb were analyzed. Texture profile analysis was determined using texture analyzer. The results showed that with the increased amount of avocado puree, the batter specific gravity increased while volume of the cakes reduced. The texture profile analysis showed that the cakes became harder as the amount of avocado puree increased, while cohesiveness was not affected. The cellular structure of the crumb exhibited a decrease in the number of air cells while the average cell size increased with addition of avocado puree. The colour analysis showed that the cake crumb became darker as the aavocado puree was increased.